2014
DOI: 10.1103/physrevb.89.155202
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine clock transitions of bismuth donors in silicon detected by spin-dependent recombination

Abstract: Bismuth donors ion-implanted in 28 Si and nat Si are studied using magnetic resonance spectroscopy based on spin-dependent recombination. The hyperfine clock transition, at which the linewidth is significantly narrowed, is observed for the bismuth donors. The experimental results are modeled quantitatively by molecular orbital theory for a coupled pair consisting of a bismuth donor and a spin-dependent recombination readout center, including the effect of hyperfine and Zeeman interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…[65] The existence of the optimal magnetic field (atomic clock transition), at which the electron decoherence was suppressed by its insensitivity to the external magnetic field perturbation was demonstrated. [66] The Keio University group investigated the hyperfine clock transition of bismuth using the magnetic field at which the resonant frequency was insensitive to fluctuations in the hyperfine constant in isotopically enriched 28 Si [67] using the spin-dependent-recombination EPR technique developed especially for this purpose. [68] The decoherence and decoupling mechanisms for the 29 Si nuclear spins as qubits were investigated with bulk nat Si and isotopically enriched IKZ 29 Si at Stanford University, USA and Keio University, Japan.…”
Section: Proof-of-concept Experiments With Spin Ensembles In Isotopicmentioning
confidence: 99%
“…[65] The existence of the optimal magnetic field (atomic clock transition), at which the electron decoherence was suppressed by its insensitivity to the external magnetic field perturbation was demonstrated. [66] The Keio University group investigated the hyperfine clock transition of bismuth using the magnetic field at which the resonant frequency was insensitive to fluctuations in the hyperfine constant in isotopically enriched 28 Si [67] using the spin-dependent-recombination EPR technique developed especially for this purpose. [68] The decoherence and decoupling mechanisms for the 29 Si nuclear spins as qubits were investigated with bulk nat Si and isotopically enriched IKZ 29 Si at Stanford University, USA and Keio University, Japan.…”
Section: Proof-of-concept Experiments With Spin Ensembles In Isotopicmentioning
confidence: 99%
“…With the rapid advancement in studies of phosphorus donor electron spins (S = 1/2) and nuclear spins (I = 1/2 of 31 P) as potential qubits in silicon-based quantum information processing, 1-4 the isotope engineering of host silicon has become very important. Elimination of the host 29 Si nuclear magnetic moments by nuclear-spin-free 28 Si isotopic enrichment led to spectral narrowing of phosphorus donor electron spin resonance (ESR) lines [5][6][7] and the coherence time extension of phosphorus electron spins 5,8 and nuclear spins. [9][10][11] The effects of host silicon isotopes ( 28 Si, 29 Si, 30 Si) are well known in a variety of impurity electric dipole transitions in silicon.…”
mentioning
confidence: 99%
“…We have found that, after the application of light and light-voltage pulses, quadrupolar effects can limit the coherence some transitions and that these influences are minimized when allowing for longer waiting times during the pulse sequence. Such decoherence could be relevant in any nuclear spins system with I > 1/2, and can be avoided by cosing optimal working points in the magnetic field and strain, equivalent to clock transitions with respect to magnetic field [16] or hyperfine interaction [17]. We have also measured echoes connected to higher-order coherences using a phase-cycling technique, exploring the full potential of the four-dimensional Hilbert space.…”
mentioning
confidence: 99%
“…Due to different interaction strengths with their surroundings, they form a powerful combination of a fast, but more volatile electron spin and a slower, but very coherent nuclear spin qubit [9][10][11]. This nuclear spin is I = 1/2 for phosphorus, but systems with a higher nuclear spin can be realized by simply replacing phosphorus by the other hydrogenic donors As (I = 3/2) [12,13], Sb (5/2 and 7/2) [14,15], and Bi (9/2) [16][17][18]. Several advantages of the d-dimensional Hilbert spaces of such systems, sometimes called qudits, have been proposed, such as the realization of simpler and more efficient gates [19,20] or more secure quantum cryptography [21].…”
mentioning
confidence: 99%